2018
DOI: 10.1021/acsenergylett.8b01315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Layer Thickness on the Charge Carrier and Spin Coherence Lifetime in Two-Dimensional Layered Perovskite Single Crystals

Abstract: We report the charge carrier recombination rate and spin coherence lifetimes in single crystals of two-dimensional (2D) Ruddlesden−Popper perovskites PEA 2 PbI 4 •(MAPbI 3 ) n−1 (PEA, phenethylammonium; MA, methylammonium; n = 1, 2, 3, 4). Layer thickness-dependent charge carrier recombination rates are observed, with the fastest rates for n = 1 because of the large exciton binding energy, and the slowest rates are observed for n = 2. Room-temperature spin coherence times also show a nonmonotonic layer thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
226
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(236 citation statements)
references
References 37 publications
8
226
2
Order By: Relevance
“…This weak electric field contributes to the DC offset current D (see MM5 in SI). However, based on our calculation, this weak electric field is not strong enough to dissociate the excitons in 2D-PEPI because of the large exciton binding energy here (>250 meV) 24,29,37 . Yet, as shown in ref.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…This weak electric field contributes to the DC offset current D (see MM5 in SI). However, based on our calculation, this weak electric field is not strong enough to dissociate the excitons in 2D-PEPI because of the large exciton binding energy here (>250 meV) 24,29,37 . Yet, as shown in ref.…”
Section: Resultsmentioning
confidence: 79%
“…Both C2/m andP 1 space groups are centrosymmetric; however, responses associated with broken inversion symmetry may still occur due to the presence of interfaces/surfaces in the MQW structure 14,27 . Giant Rashba splitting was inferred in a recent spectroscopic study of 2D-PEPI 28 and has since initiated strong interest in this material 25,26,29 . However, a direct observation of a spin-related photocurrent and the symmetry breaking direction are still missing.…”
mentioning
confidence: 99%
“…TRPL was used to examine the recombination lifetime in perovskite thin films deposited on glass substrates (Figure b). Consistent with the above results, perovskite films fabricated from DMF/DMSO (5:5) show longer carrier lifetime compared to the lifetime for the perovskite films fabricated from pure DMF . Most strikingly is the TRMC measurement of the carrier mobility.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, the photoinduced bleach TA signal reflects to all exciton population. Using TA spectroscopy, Chen et al 29 reported both k 2 and k 3 increases as n decreases; however, they interpreted the k 2 in terms of bimolecular recombination of free carriers instead of EEA. Auger recombination in mixed-phase 2D-3D perovskites has been studied by time-resolved THz measurements by Milot et al; 28 however, THz measurements are sensitive to free carriers instead of excitons.…”
Section: Resultsmentioning
confidence: 99%
“…To differentiate these two regimes, measurements of exciton population dynamics in both spatial and temporal domains are required. However, the majority of studies on exciton annihilation so far are based on time-resolved photoluminescence (PL) or transient absorption (TA) spectroscopy that offers no spatial resolution, leading to annihilation rates convoluted with exciton diffusion constants [28][29][30] , making it difficult to elucidate factors that control these two processes independently.…”
mentioning
confidence: 99%